High-temperature-resistant xanthan gum and preparation method thereof
By introducing inorganic nanomaterials with polar groups and chemical vapor deposition technology, as well as chemical crosslinking and graft polymer technology, combined with ultraviolet irradiation and amine modification of high temperature resistant polymers, xanthan gum heat at high temperatures is solved. The problem of poor stability has significantly improved its high temperature resistance.
Patent Information
- Application Number
- CN202411649124.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-14
AI Technical Summary
Xanthan gum has poor thermal stability in high-temperature environments, resulting in a decrease in functionality, making it difficult to meet the application needs of high-temperature scenarios such as oil, natural gas extraction and food processing.
By introducing polar groups and chemical vapor deposition technology, inorganic nanomaterials modified, combined with chemical crosslinking and grafting polymer technology, the intermolecular covalent bonding and structural integrity of xanthan gum are enhanced, and high-temperature resistant polymerization is introduced. The substance is subjected to ultraviolet light irradiation and amine group modification to form a stable network structure to improve thermal stability.
It significantly improves the high temperature resistance and structural stability of xanthan gum, and meets the high temperature environment needs of more industrial applications.
Smart Images

Figure CN119307017A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified xanthan gum and relates to high temperature resistant xanthan gum and a preparation method thereof. Background Art
[0002] Xanthan gum is an exopolysaccharide produced by Xanthomonas campestris through fermentation of sugars, with unique chemical structure and physical properties. After dissolving in water, xanthan gum can form a high-viscosity solution with excellent thickening, suspension, emulsification and stabilization functions. As a bio-based material, it has a wide range of applications. For example, in the food industry, xanthan gum is often used as a thickener, stabilizer and emulsifier; in oil drilling, xanthan gum is used for thickening and stabilization of drilling fluids and muds; in the cosmetics and pharmaceutical fields, xanthan gum is used as a functional additive such as a suspending agent and stabilizer. The environmental protection characteristics, good rheological properties and biocompatibility of xanthan gum make it an indispensable and important material in many industries.
[0003] However, xanthan gum has poor thermal stability and is prone to molecular chain degradation in high temperature environments, resulting in reduced functionality. The wide application of xanthan gum in high temperature scenarios such as oil and gas extraction and food processing places higher demands on the high temperature resistance of xanthan gum. Therefore, xanthan gum needs to be modified to improve its high temperature resistance. Summary of the invention
[0004] In view of the above problems, the object of the present invention is to provide a high temperature resistant xanthan gum and a preparation method thereof. By introducing the inorganic nanomaterials modified by polar groups and chemical vapor deposition, not only the heat resistance of xanthan gum is improved, but also its structural stability at high temperatures is improved. In addition, the addition of high temperature resistant polymers, especially the polymers modified by ultraviolet light and amine groups, further enhances the high temperature resistance of the material. Combined with chemical crosslinking and grafting modification technology, the present invention effectively improves the heat resistance of xanthan gum, so that it shows excellent performance stability under high temperature environment, and meets more industrial application needs.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In the first aspect, the present invention provides a high temperature resistant xanthan gum, the high temperature resistant xanthan gum comprises modified xanthan gum, polar modified nanomaterials deposited by thin films, surface activated high temperature resistant polymers modified by amino groups, and surfactants. By chemically crosslinking and co-modifying the xanthan gum with grafted polymers, the covalent bonds between molecules can be enhanced, the rigidity of the molecular chains can be increased, and the structural integrity of the materials can be improved, thereby significantly improving the high temperature resistance of the xanthan gum. The introduction of epoxy groups into the grafted polymer further enhances the compatibility and binding force between the grafted polymer and the xanthan gum, forming a more stable network structure, thereby improving the thermal stability of the material. The introduced inorganic nanomaterials improve the high temperature resistance of the xanthan gum by providing physical barriers, enhancing thermal stability, improving mechanical properties, and inhibiting pyrolysis. The introduction of polar groups into inorganic nanomaterials can enhance the compatibility of xanthan gum with inorganic nanomaterials, and the enhancement of interfacial interaction forces further improves the high temperature stability of the xanthan gum. The chemical vapor deposition film on its surface can enhance the chemical inertness and interfacial stability through the thermal barrier effect, further improving the performance of the xanthan gum under high temperature conditions. The introduction of high temperature resistant polymers can significantly improve the high temperature resistance of xanthan gum by improving thermal stability, physical barrier effect and structural reinforcement. UV irradiation and introduction of amine modification of high temperature resistant polymers can enhance the surface activity and polarity of high temperature resistant polymers, improve their compatibility with xanthan gum, and further improve the thermal stability and high temperature resistance of xanthan gum.
[0007] As a preferred technical solution of the present invention, the heat-resistant xanthan gum comprises the following components in parts by weight:
[0008]
[0009] Among them, the mass parts of modified xanthan gum can be 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts or 80 parts, the mass parts of polar modified nanomaterials deposited by thin films can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, and the mass parts of amino-modified surface-activated high temperature resistant polymers can be 5 parts, 6 parts, , 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, the mass part of the surfactant can be 0.1 part, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2.0 parts, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0010] The invention modifies xanthan gum by chemical crosslinking and grafting polymer. A covalent bond is formed between xanthan gum molecules by introducing a crosslinking agent, thereby constructing a three-dimensional crosslinking network. This crosslinking network has strong thermal stability, can maintain the integrity of the molecular chain at high temperature, and avoids the material failure caused by thermal decomposition or chain breakage of xanthan gum; secondly, the crosslinking structure reduces the mobility of the xanthan gum molecular chain by increasing the overall rigidity of the molecular chain, reduces the possibility of thermal energy causing molecular chain breakage, thereby delaying the occurrence of thermal decomposition; and in the crosslinked xanthan gum structure, due to the presence of covalent bonds, higher energy is required to destroy the chemical bonds between molecules, which improves the thermal stability and decomposition temperature of the material; at the same time, the crosslinking agent not only establishes covalent bonds between molecules, but also strengthens the hydrogen bonds and van der Waals forces between molecules. These forces can further stabilize the molecular chain at high temperature, prevent molecular disintegration or enhance the thermal motion of chain segments; and the formation of the crosslinking network significantly increases the rigidity of the xanthan gum molecular chain. This rigidity helps to maintain the structural stability of the material at high temperature, so that the material is not easy to soften or lose mechanical properties when heated. The rigid chain network structure helps to resist thermoplastic behavior caused by high temperature.
[0011] Graft modification is mainly achieved by introducing polymers with high heat resistance into the xanthan gum molecular chain. These polymers themselves have a high thermal decomposition temperature and excellent high temperature resistance, which can transfer their heat resistance to the xanthan gum molecules, thereby increasing the thermal decomposition temperature of the entire xanthan gum composite material. After polymer grafting, the xanthan gum molecular chain and the polymer form a new chemical structure, which enhances the overall thermal stability; at the same time, the grafted polymer can help disperse and evenly distribute the thermal stress under high temperature to avoid material failure caused by local overheating; secondly, the grafted polymer and the xanthan gum can form a strong interface bond, especially when the grafted polymer contains polar groups, they form a strong bond with the polar groups in the xanthan gum through hydrogen bonds or other intermolecular forces. This bond can maintain the structural integrity of the material at high temperatures and prevent the material from being delaminated or decomposed; in addition, the grafted polymer generally has a large molecular weight and a complex molecular structure, which makes the modified xanthan gum molecular chain more complex and cross-linked, thereby enhancing the thermal stability and high temperature resistance of the material. High molecular weight grafted materials can also maintain good mechanical properties at high temperatures, and are not prone to segment movement and material flow.
[0012] The introduction of epoxy groups can further enhance the binding force and thermal stability of the grafted polymer and xanthan gum through chemical reactions. The epoxy group has high reactivity and can undergo a ring-opening reaction with polar groups such as hydroxyl and amine groups in the xanthan gum molecule to form a strong chemical bond. The covalent bond formed by this chemical reaction further improves the compatibility and interfacial bonding between the grafted polymer and xanthan gum. The covalent bond formed after the epoxy group is opened is stronger than the hydrogen bond and van der Waals force, and can be more stable under high temperature conditions, thereby preventing the material from decomposing or separating at high temperatures; and the more stable chemical structure formed by the ring-opening reaction of the epoxy group can maintain the integrity of the material at high temperatures and improve the high temperature resistance of the xanthan gum composite material; at the same time, the introduction of epoxy groups can further increase the cross-linking degree of the grafted polymer and form a denser three-dimensional network structure. This network structure can not only enhance the mechanical properties of the material, but also effectively improve the heat resistance of the material; at the same time, the stable structure formed by the chemical reaction between the epoxy group and the grafted polymer is not easy to undergo thermal decomposition under high temperature conditions, which can effectively delay the decomposition process of the xanthan gum matrix. In addition, the grafted polymer modified with epoxy groups can further reduce the thermal motion of xanthan gum molecular chains and improve the thermal stability of the material at high temperatures.
[0013] The present invention introduces inorganic nanomaterials to modify xanthan gum. The inorganic nanomaterials have a high melting point and high thermal stability, and when dispersed in a xanthan gum matrix, a physical barrier layer can be formed. This barrier effect can slow down the conduction of heat, thereby improving the tolerance of xanthan gum under high temperature conditions; at the same time, the nanomaterials themselves have high thermal stability, and they can enhance the structural stability of xanthan gum by physical doping or chemical bonding. When the nanoparticles are uniformly dispersed in the matrix, they can effectively disperse thermal stress and prevent the xanthan gum from decomposing or thermally failing at high temperatures; in addition, the inorganic nanomaterials can generally enhance the mechanical properties of the xanthan gum composite material, such as improving the modulus and strength of the xanthan gum. At high temperatures, the mechanical properties of xanthan gum decrease rapidly, but the introduced nanomaterials can play a reinforcing role, so that it still maintains good mechanical properties at high temperatures; and xanthan gum is a natural polymer with limited heat resistance. When the temperature rises, the xanthan gum is prone to thermal decomposition reaction to generate small molecules. Inorganic nanomaterials can inhibit the thermal decomposition reaction of xanthan gum through physical or chemical effects on its molecular chains, thereby improving its high temperature resistance.
[0014] Xanthan gum is a hydrophilic natural polymer with a certain polarity. However, the surface of unmodified inorganic nanomaterials is usually hydrophobic, resulting in poor compatibility between the two and easy agglomeration or separation. Therefore, the present invention introduces polar groups on the surface of nanomaterials, which can improve the interaction between nanomaterials and xanthan gum molecular chains, enhance interfacial compatibility, and thus form a more stable composite structure; polar groups such as aminosilane can chemically bond or hydrogen bond with hydroxyl groups or other polar groups in xanthan gum, which can form a strong interface bond between nanomaterials and xanthan gum matrix, which not only improves the overall stability of the composite material, but also makes it difficult for nanomaterials to break away from the xanthan gum matrix at high temperatures, thereby improving high temperature resistance; and the introduction of polar groups can also form a protective coating on the surface of inorganic nanomaterials, slowing down the agglomeration or thermal failure of nanoparticles at high temperatures. Through this surface polarity modification, nanomaterials can maintain their dispersibility and stability at higher temperatures, thereby further improving the high temperature resistance of composite materials.
[0015] Thin films deposited by chemical vapor deposition usually have excellent thermal barrier properties. This film can form a thermal resistance layer on the surface of the nanomaterial, further blocking the conduction and diffusion of heat, thereby improving its high temperature resistance; thin films formed on the surface of inorganic nanomaterials by chemical vapor deposition usually have high chemical inertness and thermal stability. For example, silane-based films are not easy to decompose or oxidize at high temperatures. This chemical inertness can further protect the nanomaterial and keep it stable for a long time in the xanthan gum composite material; at the same time, the deposited film can also improve the interface stability between the nanomaterial and the xanthan gum matrix. After the nanomaterial is modified by deposition, the surface chemical properties are more uniform and stable, and it can form a stronger interface bonding force with xanthan gum to prevent interface damage at high temperatures.
[0016] The present invention limits the mass fraction of polar modified nanomaterials deposited in the thin film to 1-10 parts. When the content is too high, the particles may agglomerate, resulting in uneven dispersion, weakened interface effects, and even destruction of the structural continuity of the material. At the same time, a high content of nanomaterials may make the material brittle, resulting in decreased flexibility, and reduce the impact resistance of the material, which may weaken the high temperature resistance of xanthan gum.
[0017] The present invention introduces a high temperature resistant polymer to modify xanthan gum. The introduction of the high temperature resistant polymer can effectively increase the thermal decomposition temperature of xanthan gum. Xanthan gum itself is a natural polysaccharide, and its molecular structure is easily pyrolyzed at high temperatures. By introducing a high temperature resistant polymer with high thermal stability, it can play a dilution and isolation role, reduce the direct impact of heat on xanthan gum molecules, and thus delay the thermal decomposition process of xanthan gum; at the same time, the high temperature resistant polymer is evenly distributed in the xanthan gum matrix and can act as a physical barrier to hinder heat conduction. Under high temperature conditions, the presence of these polymers will slow down the transfer of heat, forming a protective barrier, and reducing the thermal decomposition rate inside the xanthan gum. This physical barrier effect is very important for improving the thermal stability of the material; in addition, the rigid structure of the high temperature resistant polymer can enhance the mechanical strength of the xanthan gum, especially under high temperature conditions. As the temperature rises, the xanthan gum may soften or lose its structural integrity, while the rigidity and heat resistance of the high temperature resistant polymer can maintain the structural stability of the composite material and prevent thermal deformation and performance degradation.
[0018] UV irradiation can induce free radical reactions on the surface of the heat-resistant polymer to form active sites. These active sites can promote subsequent chemical modification processes, such as the introduction of amine groups. UV irradiation may also induce surface micro-crosslinking or mild oxidation, making the surface of the heat-resistant polymer more susceptible to interaction with xanthan gum and enhancing the interfacial bonding of the composite material.
[0019] The introduction of amine groups can significantly enhance the chemical compatibility between high temperature resistant polymers and xanthan gum. The amine groups can form hydrogen bonds with the hydroxyl groups or other polar groups in xanthan gum to form a strong interfacial bond. This chemical bond not only enhances the compatibility of the two materials, but also improves the mechanical strength and thermal stability of xanthan gum. The introduction of amine groups can also improve the dispersibility of the composite material and avoid stratification or uneven dispersion of the material at high temperatures.
[0020] The dual modification of ultraviolet light and the introduction of amine groups also has a synergistic effect on the high temperature resistance of high temperature resistant polymers: ultraviolet light irradiation activates the surface of high temperature resistant polymers, making them more susceptible to reaction with amine reagents. After the introduction of polar amine groups, the interface bonding of the material and the interaction between molecular chains are enhanced. Under high temperature conditions, the improvement of the interface bonding strength can better maintain the structural stability of the xanthan gum matrix, thereby significantly improving its high temperature resistance. This synergistic effect can protect xanthan gum through both chemical and physical effects and reduce the thermal decomposition rate of the material.
[0021] The present invention limits the mass parts of the surface activated high temperature resistant polymer modified by the amino group to 5-15 parts. When the content of the high temperature resistant polymer is moderate, the overall performance of the material can achieve an optimized effect. After ultraviolet light irradiation and the introduction of the amino group, the interface of the high temperature resistant polymer and the xanthan gum is relatively sufficient, and a uniform composite structure can be formed, thereby improving the thermal stability, mechanical strength and heat resistance of the material. However, when the content is too high, the interaction between the modified high temperature resistant polymers may be too strong, resulting in a weakening of the interface bonding force with the xanthan gum; and a high content of high temperature resistant polymers generally exhibits a strong rigidity, resulting in a decrease in the flexibility of the xanthan gum composite material. Under high temperature conditions, the brittleness of the material increases, which may cause stress concentration and structural damage; at the same time, a high content of high temperature resistant polymers may form agglomeration in the xanthan gum matrix, affecting the uniformity of the material, resulting in premature thermal decomposition in the local area, and the overall high temperature resistance performance is reduced.
[0022] In a second aspect, the present invention provides a method for preparing high temperature resistant xanthan gum, the preparation method comprising:
[0023] S1: dissolving a polar group reagent in anhydrous ethanol, adding deionized water to obtain a polar group solution, adding an inorganic nanomaterial, stirring and dispersing the solution, filtering, washing, and drying to obtain an inorganic nanomaterial with surface polarity modification; placing the inorganic nanomaterial with surface polarity modification into a chemical vapor deposition device for deposition modification, and drying after the deposition to obtain a polarity-modified nanomaterial with thin film deposition;
[0024] S2: placing the high temperature resistant polymer in an ultraviolet irradiation device for irradiation; cooling to obtain a surface activated high temperature resistant polymer; dissolving the amination reagent in a mixed solvent of anhydrous ethanol and deionized water to obtain an amination grafting solution, immersing the surface activated high temperature resistant polymer therein, and adding an amination catalyst to obtain a reaction solution A, stirring the reaction at a constant temperature, filtering, washing, and drying to obtain an amino-modified surface activated high temperature resistant polymer;
[0025] S3: Dissolve xanthan gum in deionized water and stir to obtain a xanthan gum solution; add a polyol and a catalyst to obtain a mixed solution A, use a sodium hydroxide solution to adjust the pH of the mixed solution A to obtain a reaction solution B, react in a constant temperature water bath, and cool the reaction solution B for standby use after the reaction is completed; add a grafted polymer to deionized water to obtain a grafted solution, add an epoxy group donor to the grafted solution and stir to obtain a mixed solution B, add azobisisobutyronitrile to obtain a reaction solution C, stir at a constant temperature under an inert gas atmosphere, add anhydrous ethanol to precipitate after cooling, filter, wash, and dry to obtain an epoxy group-modified grafted polymer; dissolve the epoxy group-modified grafted polymer in deionized water to obtain an epoxy group-modified grafted polymer solution, add the epoxy group-modified grafted polymer to the cooled reaction solution B and stir to obtain a mixed solution C, add a cross-linking agent to the mixed solution C and continue stirring to obtain a reaction solution D, stir at a constant temperature, add anhydrous ethanol to precipitate after cooling, filter, wash, and dry to obtain a modified xanthan gum;
[0026] S4: Dispersing the modified xanthan gum in deionized water and stirring to disperse, then adding the polar modified nanomaterial deposited by thin film, the surface activated high temperature resistant polymer modified by amine group and the surfactant to obtain the reaction solution E, stirring and drying to obtain the high temperature resistant xanthan gum.
[0027] As a preferred technical solution of the present invention, in step S1, the volume fraction of polar groups in the polar group solution is 2-5%, for example, it can be 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8% or 5%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In some optional examples, the amount of deionized water added is 0.5-1 mL, for example, it can be 0.5 mL, 0.55 mL, 0.6 mL, 0.65 mL, 0.7 mL, 0.75 mL, 0.8 mL, 0.85 mL, 0.9 mL, 0.95 mL or 1.0 mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional examples, the mass ratio of the polar group reagent to the inorganic nanomaterial is 1:(3-5), for example, it can be 1:3, 1:3.2, 1:3.4, 1:3.6, 1:3.8, 1:4, 1:4.2, 1:4.4, 1:4.6, 1:4.8 or 1:5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional examples, the stirring and dispersion time after the inorganic nanomaterial is added to the polar group solution is 40-60 min, for example, it can be 40 min, 42 min, 44 min, 46 min, 48 min, 50 min, 52 min, 54 min, 56 min, 58 min or 60 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional examples, the drying temperature of the surface polarity modified inorganic nanomaterial is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional examples, the drying time of the surface polarity modified inorganic nanomaterial is 24-30h, for example, it can be 24h, 24.5h, 25h, 25.5h, 26h, 26.5h, 27h, 27.5h, 28h, 28.5h, 29h, 29.5h or 30h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In some optional examples, the temperature for deposition modification of the surface polarity-modified inorganic nanomaterial is 250-350°C, for example, it can be 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C or 350°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional examples, the deposition modification time of the surface polarity-modified inorganic nanomaterial is 1-2 h, for example, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In some optional examples, the gas pressure for deposition modification of the surface polarity-modified inorganic nanomaterial is 1-5 Torr, for example, 1 Torr, 1.5 Torr, 2 Torr, 2.5 Torr, 3 Torr, 3.5 Torr, 4 Torr, 4.5 Torr or 5 Torr, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional examples, the drying temperature of the thin film deposited polar modified nanomaterial is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional examples, the drying time of the thin film deposited polar modified nanomaterial is 8-12 hours, for example, it can be 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] As a preferred technical solution of the present invention, in step S2, the wavelength of the ultraviolet light source in the ultraviolet light irradiation equipment is 220-260nm, for example, it can be 220nm, 225nm, 230nm, 235nm, 240nm, 245nm, 250nm, 255nm or 260nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional embodiments, the ultraviolet light intensity in the ultraviolet light irradiation device is 10-20W / cm 2 , for example, it can be 10W / cm 2 , 11W / cm 2 、12W / cm 2 、13W / cm 2 、14W / cm 2 , 15W / cm 2 、16W / cm 2 、17W / cm 2 、18W / cm 2 、19W / cm 2 or 20W / cm 2 , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In some optional instances, the ultraviolet light irradiation time in the ultraviolet light irradiation equipment is 15-30 min, for example, it can be 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional examples, the volume ratio of anhydrous ethanol and deionized water in the mixed solvent of the aminated grafting solution is (7:3)-(9:1), for example, it can be 7:3, 8:2 or 9:1, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some optional examples, the concentration of the amination agent in the amination grafting solution is 0.1-1.0 M, for example, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M, 0.6 M, 0.7 M, 0.8 M, 0.9 M or 1.0 M, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some optional examples, the mass ratio of the surface activated high temperature resistant polymer to the aminated reagent is 1:(5-10), for example, it can be 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In some optional examples, the amination catalyst accounts for 0.1-0.5% of the mass of the surface-activated high temperature resistant polymer, for example, it can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some optional examples, the temperature of the constant temperature stirring of the reaction liquid A is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional examples, the constant temperature stirring time of the reaction solution A is 1-2h, for example, it can be 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional examples, the drying temperature of the amino-modified surface-activated high temperature resistant polymer is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In some optional examples, the drying time of the amino-modified surface-activated high temperature resistant polymer is 20-30 hours, for example, it can be 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours or 30 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] As a preferred technical solution of the present invention, in step S3, the proportion of xanthan gum in the xanthan gum solution is 1-2%, for example, it can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some optional examples, the temperature at which the xanthan gum solution is stirred is 25-35°C, for example, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional examples, the stirring time of the xanthan gum solution is 1-2h, for example, it can be 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In some optional examples, the polyol accounts for 20-30% of the mass of the xanthan gum, for example, it can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some optional examples, the catalyst accounts for 0.1-0.5% of the mass of xanthan gum, for example, it can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some optional examples, the pH of the mixed solution A is adjusted to 8-10 to obtain reaction solution B, for example, it can be 8.0, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8 or 10.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some optional examples, the temperature of the constant temperature water bath reaction of the reaction liquid B is 50-70°C, for example, it can be 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In some optional examples, the constant temperature water bath reaction time of the reaction solution B is 3-4h, for example, it can be 3h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h or 4h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional examples, the concentration of the grafting solution is 0.2-0.4 g / mL, for example, it can be 0.2 g / mL, 0.22 g / mL, 0.24 g / mL, 0.26 g / mL, 0.28 g / mL, 0.3 g / mL, 0.32 g / mL, 0.34 g / mL, 0.36 g / mL, 0.38 g / mL or 0.4 g / mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional examples, the mass ratio of the epoxy group donor to the grafted polymer is (1-2):10, for example, it can be 1:10, 1.1:10, 1.2:10, 1.3:10, 1.4:10, 1.5:10, 1.6:10, 1.7:10, 1.8:10, 1.9:10 or 2:10, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In some optional examples, the mass ratio of azobisisobutyronitrile to the grafted polymer is (1-2):100, for example, it can be 1:100, 1.1:100, 1.2:100, 1.3:100, 1.4:100, 1.5:100, 1.6:100, 1.7:100, 1.8:100, 1.9:100 or 2:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In some optional examples, the constant temperature stirring temperature of the reaction liquid C is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In some optional examples, the constant temperature stirring time of the reaction liquid C is 2-3h, for example, it can be 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In some optional examples, the drying temperature of the epoxy group modified graft polymer is 40-50°C, for example, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some optional examples, the drying time of the epoxy group modified graft polymer is 18-24 hours, for example, it can be 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] In some optional examples, the concentration of the epoxy group modified graft polymer solution is 0.04-0.08 g / mL, for example, it can be 0.04 g / mL, 0.045 g / mL, 0.05 g / mL, 0.055 g / mL, 0.06 g / mL, 0.065 g / mL, 0.07 g / mL, 0.075 g / mL or 0.08 g / mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] In some optional examples, the mass ratio of the epoxy group modified graft polymer to xanthan gum in the mixed solution C is 1:(1-2), for example, it can be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In some optional examples, the cross-linking agent accounts for 3-5% of the mass of xanthan gum, for example, it can be 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8% or 5.0%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] In some optional examples, after adding the cross-linking agent to the mixed solution, stirring is continued for 30-40 minutes, for example, 30 minutes, 31 minutes, 32 minutes, 33 minutes, 34 minutes, 35 minutes, 36 minutes, 37 minutes, 38 minutes, 39 minutes or 40 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] In some optional examples, the constant temperature stirring temperature of the reaction liquid C is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] In some optional examples, the constant temperature stirring time of the reaction liquid C is 2-3h, for example, it can be 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] In some optional examples, the drying temperature of the modified xanthan gum is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] In some optional examples, the drying time of the modified xanthan gum is 12-18 hours, for example, it can be 12 hours, 12.5 hours, 13 hours, 13.5 hours, 14 hours, 14.5 hours, 15 hours, 15.5 hours, 16 hours, 16.5 hours, 17 hours, 17.5 hours or 18 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] As a preferred technical solution of the present invention, in step S4, the modified xanthan gum is dispersed in deionized water and stirred at a speed of 500-1000rpm, for example, it can be 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm, 800rpm, 850rpm, 900rpm, 950rpm or 1000rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] In some optional examples, the modified xanthan gum is dispersed in deionized water and stirred for 1-2 hours, for example, 1 hour, 1.1 hours, 1.2 hours, 1.3 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours or 2 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] In some optional examples, the stirring temperature of the reaction liquid D is 25-35°C, for example, it can be 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] In some optional examples, the stirring time of the reaction liquid D is 30-60 min, for example, it can be 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, 42 min, 44 min, 46 min, 48 min, 50 min, 52 min, 54 min, 56 min, 58 min or 60 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] In some optional examples, the drying temperature of the high temperature resistant xanthan gum is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0077] In some optional examples, the drying time of the heat-resistant xanthan gum is 12-24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] Compared with the prior art, the present invention has the following beneficial effects:
[0079] Chemical cross-linking and grafting of polymers to xanthan gum can enhance the covalent bond between molecules, increase the rigidity of the molecular chain, and improve the structural integrity of the material, thereby significantly improving the high temperature resistance of xanthan gum. The introduction of epoxy groups into the grafted polymer further enhances the compatibility and binding force between the grafted polymer and xanthan gum, forming a more stable network structure, thereby improving the thermal stability of the material. The introduced inorganic nanomaterials improve the high temperature resistance of xanthan gum by providing physical barriers, enhancing thermal stability, improving mechanical properties, and inhibiting thermal decomposition. The introduction of polar groups into inorganic nanomaterials can enhance the compatibility of xanthan gum with inorganic nanomaterials, and the enhancement of interfacial interaction forces further improves the high temperature stability of xanthan gum. Chemical vapor deposition of thin films on its surface can enhance chemical inertness and interfacial stability through thermal barrier effects, further improving the performance of xanthan gum under high temperature conditions. The introduction of high temperature resistant polymers can significantly improve the high temperature resistance of xanthan gum by improving thermal stability, physical barrier effects, and structural enhancement. Irradiating the high temperature resistant polymer with ultraviolet light and introducing amine modification improves its compatibility with xanthan gum by enhancing the surface activity and polarity of the high temperature resistant polymer, thereby further improving the thermal stability and high temperature resistance of xanthan gum. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 A flow chart of the preparation method of the heat-resistant xanthan gum provided in Examples 1-4 of the present invention;
[0081] Figure 2 This is a comparison chart of the viscosity properties of the high temperature resistant xanthan gum prepared in Examples 1-4 of the present invention and Comparative Examples 1-4 and the xanthan gum without any treatment. DETAILED DESCRIPTION
[0082] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0083] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications, manufacturers and other information are as follows:
[0084] Aminosilane: purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd.;
[0085] 3-Aminopropyltriethoxysilane: purchased from Nanjing Quanxi New Materials Co., Ltd.;
[0086] Anhydrous ethanol: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0087] Nano-silicon dioxide: purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.;
[0088] Nano-alumina: purchased from Yurui (Shanghai) Chemical Co., Ltd.
[0089] Polytetrafluoroethylene: purchased from Shanghai Hanluo New Materials Co., Ltd.
[0090] Polyimide: purchased from Shanghai Xuerong Chemical Technology Co., Ltd.;
[0091] Polyetheretherketone: purchased from Guangdong Yunxing Biotechnology Co., Ltd.;
[0092] Ethylenediamine: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0093] Hexamethylenediamine: purchased from Nanjing Blue and White Chemical Co., Ltd.
[0094] Benzoyl peroxide: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0095] Dicumyl peroxide: purchased from Sinopharm Chemical Reagent Co., Ltd.
[0096] Xanthan gum: purchased from Hebei Fengchuan Biotechnology Co., Ltd.;
[0097] Ethylene glycol: purchased from Shandong Mantanghong New Materials Co., Ltd.;
[0098] Pentanediol: purchased from Shanghai Qiao Chemical Technology Co., Ltd.;
[0099] Tetrabutyl titanate: purchased from Jinan Jinbang Environmental Protection Technology Co., Ltd.;
[0100] Tetraisopropyl titanate: purchased from Sinopharm Chemical Reagent Co., Ltd.
[0101] Polyvinyl alcohol: purchased from Hefei Tianjian Chemical Co., Ltd.
[0102] Polyacrylic acid: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0103] Ethylene oxide: purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;
[0104] Glycidyl methacrylate: purchased from Qingdao Reinars Polymer Materials Co., Ltd.
[0105] Azobisisobutyronitrile: purchased from Shanggai Aladdin Biochemical Technology Co., Ltd.;
[0106] Glutaraldehyde: purchased from Hefei Tianjian Chemical Co., Ltd.
[0107] Hexamethylene diisocyanate: purchased from Shanghai Yien Chemical Technology Co., Ltd.
[0108] Sodium dodecyl sulfate: purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;
[0109] Polyvinyl pyrrolidone: purchased from Hefei Tianjian Chemical Co., Ltd.
[0110] Example 1
[0111] This embodiment provides a high temperature resistant xanthan gum and a preparation method thereof, wherein the high temperature resistant xanthan gum comprises the following components in parts by weight:
[0112]
[0113] The preparation method specifically comprises the following steps:
[0114] S1: dissolving aminosilane in anhydrous ethanol, adding 1 mL of deionized water to obtain a polar group solution, wherein the volume fraction of aminosilane is 2%, adding nano-silica and stirring and dispersing for 60 minutes, wherein the mass ratio of aminosilane to nano-silica is 1:5, filtering, washing, and drying at 55°C for 27 hours to obtain surface polarity-modified nano-silica; placing the surface polarity-modified nano-silica into a chemical vapor deposition device for deposition modification, wherein the deposition modification temperature is 300°C; the time is 1.5 hours; the gas pressure is 1 Torr; the gas source is silane, and after the deposition is completed, drying at 70°C for 12 hours to obtain thin film deposited polarity-modified nano-silica;
[0115] S2: Place polytetrafluoroethylene in a UV irradiation device, where the UV light source wavelength is 245nm and the UV light intensity is 10W / cm 2 ; The irradiation time is 30 minutes; after cooling, surface activated polytetrafluoroethylene is obtained; ethylenediamine is dissolved in a mixed solvent of anhydrous ethanol and deionized water to obtain an ethylenediamine grafting solution, wherein the volume ratio of anhydrous ethanol to deionized water is 7:3; the concentration of the ethylenediamine grafting solution is 1.0M, the surface activated polytetrafluoroethylene is immersed therein, the mass ratio of the surface activated polytetrafluoroethylene to the ethylenediamine is 1:5, and 0.1% of benzoyl peroxide, based on the mass of the surface activated polytetrafluoroethylene, is added to obtain a reaction solution A, the reaction is stirred at a constant temperature of 70°C for 1.5 hours, filtered, washed, and dried at 60°C for 30 hours to obtain amino-modified surface activated polytetrafluoroethylene;
[0116] S3: Dissolve xanthan gum in deionized water, and stir at 25°C for 2h to obtain a xanthan gum solution, wherein the xanthan gum accounts for 1%; add ethylene glycol and tetrabutyl titanate to obtain a mixed solution A, wherein the ethylene glycol added accounts for 20% of the mass of the xanthan gum; the tetrabutyl titanate accounts for 0.1% of the mass of the xanthan gum, and use sodium hydroxide solution to adjust the pH of the mixed solution A to 10 to obtain a reaction solution B, and react in a 60°C constant temperature water bath for 3.5h. After the reaction, cool the reaction solution B for later use; add polyvinyl alcohol to deionized water to obtain a polyvinyl alcohol grafted solution with a concentration of 0.2g / mL, add ethylene oxide to the polyvinyl alcohol grafted solution, and stir to obtain a mixed solution B, wherein the mass ratio of ethylene oxide to polyvinyl alcohol is 1.5:10, and add azobisisobutyronitrile to obtain a reaction solution C, wherein azobisisobutyronitrile The mass ratio of nitrile to polyvinyl alcohol is 2:100, and the mixture is stirred at a constant temperature of 65°C for 2.5 hours under a nitrogen atmosphere. After cooling, anhydrous ethanol is added to precipitate, which is filtered, washed, and dried at 47°C for 19 hours to obtain epoxy group-modified polyvinyl alcohol; the epoxy group-modified polyvinyl alcohol is dissolved in deionized water to obtain an epoxy group-modified polyvinyl alcohol solution with a concentration of 0.04 g / mL, which is added to the cooled reaction solution B and stirred to obtain a mixed solution C, wherein the mass ratio of epoxy group-modified polyvinyl alcohol to xanthan gum is 1:1.5, and glutaraldehyde accounting for 3% of the mass of xanthan gum is added to the mixed solution C and stirred for 30 minutes to obtain a reaction solution D, which is stirred at a constant temperature of 70°C for 2 hours, and after cooling, anhydrous ethanol is added to precipitate, which is filtered, washed, and dried at 50°C for 18 hours to obtain modified xanthan gum;
[0117] S4: Disperse the modified xanthan gum in deionized water and stir to disperse it, wherein the stirring speed is 1000 rpm; the time is 1 hour, then add the polar modified nano-silica deposited by thin film, amino-modified surface activated polytetrafluoroethylene and sodium dodecyl sulfate to obtain reaction solution E, stir at 30°C for 45 minutes and dry to obtain high temperature resistant xanthan gum, wherein the drying temperature is 55°C and the time is 20 hours.
[0118] Example 2
[0119] This embodiment provides a high temperature resistant xanthan gum and a preparation method thereof, wherein the high temperature resistant xanthan gum comprises the following components in parts by weight:
[0120]
[0121] The preparation method specifically comprises the following steps:
[0122] S1: dissolving aminosilane in anhydrous ethanol, adding 0.5 mL of deionized water to obtain a polar group solution, wherein the volume fraction of aminosilane is 5%, adding nano-alumina and stirring and dispersing for 50 minutes, wherein the mass ratio of aminosilane to nano-alumina is 1:4.5, filtering, washing, and drying at 50°C for 30 hours to obtain surface polarity-modified nano-alumina; placing the surface polarity-modified nano-alumina into a chemical vapor deposition device for deposition modification, wherein the deposition modification temperature is 350°C; the time is 1 hour; the gas pressure is 5 Torr; the gas source is silane, and after the deposition is completed, drying at 80°C for 8 hours to obtain a thin film deposited polarity-modified nano-alumina;
[0123] S2: Place the polyimide in a UV irradiation device, where the UV light source has a wavelength of 260nm and the UV light intensity is 15W / cm 2 ; The irradiation time is 22 minutes; after cooling, a surface-activated polyimide is obtained; hexamethylenediamine is dissolved in a mixed solvent of anhydrous ethanol and deionized water to obtain a hexamethylenediamine grafting solution, wherein the volume ratio of anhydrous ethanol to deionized water is 8:2; the concentration of the hexamethylenediamine grafting solution is 0.8M, the surface-activated polyimide is immersed therein, the mass ratio of the surface-activated polyimide to hexamethylenediamine is 1:7.5, and 0.25% of benzoyl peroxide, based on the mass of the surface-activated polyimide, is added to obtain a reaction solution A, the reaction is stirred at a constant temperature of 60°C for 2 hours, filtered, washed, and dried at 64°C for 27 hours to obtain an amino-modified surface-activated polyimide;
[0124] S3: Dissolve xanthan gum in deionized water, stir at 30°C for 1.5h to obtain a xanthan gum solution, wherein the xanthan gum accounts for 1.5%; add pentanediol and tetrabutyl titanate to obtain a mixed solution A, wherein the added pentanediol accounts for 25% of the mass of the xanthan gum; the tetrabutyl titanate accounts for 0.3% of the mass of the xanthan gum, use sodium hydroxide solution to adjust the pH of the mixed solution A to 8 to obtain a reaction solution B, and react in a 70°C constant temperature water bath for 3h. After the reaction, cool the reaction solution B for later use; add polyacrylic acid to deionized water to obtain a polyacrylic acid grafted solution with a concentration of 0.3g / mL, add ethylene oxide to the polyacrylic acid grafted solution and stir to obtain a mixed solution B, wherein the mass ratio of ethylene oxide to polyacrylic acid is 1:10, and add azobisisobutyronitrile to obtain a reaction solution C, wherein azobisisobutyronitrile and polypropylene The mass ratio of the acid is 1:100, and the reaction is stirred at a constant temperature of 68°C for 2.2 hours under an argon atmosphere. After cooling, anhydrous ethanol is added to precipitate, which is filtered, washed, and dried at 45°C for 22.5 hours to obtain epoxy group-modified polyacrylic acid; the epoxy group-modified polyacrylic acid is dissolved in deionized water to obtain an epoxy group-modified polyacrylic acid solution with a concentration of 0.08 g / mL, which is added to the cooled reaction solution B and stirred to obtain a mixed solution C, wherein the mass ratio of the epoxy group-modified polyacrylic acid to the xanthan gum is 1:1.7, and hexamethylene diisocyanate accounting for 4% of the mass of the xanthan gum is added to the mixed solution C and continued to stir for 37 minutes to obtain a reaction solution D, which is stirred at a constant temperature of 60°C for 3 hours, and after cooling, anhydrous ethanol is added to precipitate, which is filtered, washed, and dried at 58°C for 14 hours to obtain modified xanthan gum;
[0125] S4: Disperse the modified xanthan gum in deionized water and stir to disperse it, wherein the stirring speed is 500 rpm; the time is 2 hours, then add the polar modified nano alumina deposited by thin film, the surface activated polyimide modified by amino group and sodium dodecyl sulfate, polyvinyl pyrrolidone to obtain the reaction solution E, stir at 25 ℃ for 60 minutes, and dry to obtain the high temperature resistant xanthan gum, wherein the drying temperature is 58 ℃, and the time is 16 hours.
[0126] Example 3
[0127] This embodiment provides a high temperature resistant xanthan gum and a preparation method thereof, wherein the high temperature resistant xanthan gum comprises the following components in parts by weight:
[0128]
[0129]
[0130] The preparation method specifically comprises the following steps:
[0131] S1: Dissolve 3-aminopropyltriethoxysilane in anhydrous ethanol, add 0.7 mL of deionized water to obtain a polar group solution, wherein the volume fraction of 3-aminopropyltriethoxysilane is 3%, add nano-silicon dioxide and stir and disperse for 40 minutes, wherein the mass ratio of 3-aminopropyltriethoxysilane to nano-silicon dioxide is 1:4, filter, wash, and dry at 60°C for 24 hours to obtain surface polar modified nano-silicon dioxide; put the surface polar modified nano-silicon dioxide into a chemical vapor deposition device for deposition modification, wherein the deposition modification temperature is 320°C; the time is 1.2 hours; the gas pressure is 2.5 Torr; the gas source is dimethylsilane, and after the deposition is completed, dry at 77°C for 9 hours to obtain a thin film deposited polar modified nano-silicon dioxide;
[0132] S2: Place the polyetheretherketone in a UV irradiation device, where the UV light source wavelength is 220nm and the UV light intensity is 20W / cm 2 ; The irradiation time is 15 min; after cooling, the surface activated polyetheretherketone is obtained; ethylenediamine is dissolved in a mixed solvent of anhydrous ethanol and deionized water to obtain an ethylenediamine grafting solution, wherein the volume ratio of anhydrous ethanol to deionized water is 9:1; the concentration of the ethylenediamine grafting solution is 0.5 M, the surface activated polyetheretherketone is immersed therein, the mass ratio of the surface activated polyetheretherketone to ethylenediamine is 1:8.5, and 0.38% of diisopropylbenzene peroxide by mass of the surface activated polyetheretherketone is added to obtain a reaction solution A, the reaction is stirred at a constant temperature of 80°C for 1 hour, filtered, washed, and dried at 68°C for 22 hours to obtain an amino-modified surface activated polyetheretherketone;
[0133] S3: Dissolve xanthan gum in deionized water, and stir at 35°C for 1h to obtain a xanthan gum solution, wherein the xanthan gum accounts for 1.8%; add ethylene glycol and tetraisopropyl titanate to obtain a mixed solution A, wherein the added ethylene glycol accounts for 27% of the mass of the xanthan gum; the tetraisopropyl titanate accounts for 0.42% of the mass of the xanthan gum, and use sodium hydroxide solution to adjust the pH of the mixed solution A to 9 to obtain a reaction solution B, and react in a 50°C constant temperature water bath for 4h. After the reaction, cool the reaction solution B for later use; add polyvinyl alcohol to deionized water to obtain a polyvinyl alcohol grafted solution with a concentration of 0.4g / mL, add ethylene oxide to the polyvinyl alcohol grafted solution and stir to obtain a mixed solution B, wherein the mass ratio of ethylene oxide to polyvinyl alcohol is 1.8:10, and add azobisisobutyronitrile to obtain a reaction solution C, wherein the mass ratio of azobisisobutyronitrile to polyvinyl alcohol is 1.8:10. The ratio of epoxy group-modified polyvinyl alcohol to xanthan gum is 1.5:100, and the mixture is stirred at a constant temperature of 60°C for 3 hours under an argon atmosphere. After cooling, anhydrous ethanol is added to precipitate, which is filtered, washed, and dried at 50°C for 19 hours, 22.5 hours, 18 hours, and 24 hours to obtain epoxy group-modified polyvinyl alcohol; the epoxy group-modified polyvinyl alcohol is dissolved in deionized water to obtain an epoxy group-modified polyvinyl alcohol solution with a concentration of 0.07 g / mL, which is added to the cooled reaction solution B and stirred to obtain a mixed solution C, wherein the mass ratio of epoxy group-modified polyvinyl alcohol to xanthan gum is 1:1, and hexamethylene diisocyanate accounting for 4.5% of the mass of xanthan gum is added to the mixed solution C and stirred for 35 minutes to obtain a reaction solution D, which is stirred at a constant temperature of 65°C for 2.5 hours, and after cooling, anhydrous ethanol is added to precipitate, which is filtered, washed, and dried at 60°C for 12 hours to obtain modified xanthan gum;
[0134] S4: Disperse the modified xanthan gum in deionized water and stir to disperse it, wherein the stirring speed is 850 rpm; the time is 1.5 hours, then add the polar modified nano-silica deposited by thin film, the surface activated polyether ether ketone modified by amino group and polyvinyl pyrrolidone to obtain the reaction solution E, stir at 35°C for 30 minutes, and dry to obtain the high temperature resistant xanthan gum, wherein the drying temperature is 50°C and the time is 24 hours.
[0135] Example 4
[0136] This embodiment provides a high temperature resistant xanthan gum and a preparation method thereof, wherein the high temperature resistant xanthan gum comprises the following components in parts by weight:
[0137]
[0138] The preparation method specifically comprises the following steps:
[0139] S1: Dissolve 3-aminopropyltriethoxysilane in anhydrous ethanol, add 0.8 mL of deionized water to obtain a polar group solution, wherein the volume fraction of 3-aminopropyltriethoxysilane is 4%, add nano-alumina and stir and disperse for 55 minutes, wherein the mass ratio of 3-aminopropyltriethoxysilane to nano-alumina is 1:3, filter, wash, and dry at 58°C for 28.5 hours to obtain surface polarity-modified nano-alumina; put the surface polarity-modified nano-alumina into a chemical vapor deposition device for deposition modification, wherein the deposition modification temperature is 250°C; the time is 2 hours; the gas pressure is 3 Torr; the gas source is dimethylsilane, and after the deposition is completed, dry at 75°C for 10 hours to obtain a thin film deposited polarity-modified nano-alumina;
[0140] S2: Place polytetrafluoroethylene in a UV irradiation device, where the UV light source wavelength is 250nm and the UV light intensity is 18W / cm 2 ; The irradiation time is 18 minutes; after cooling, surface activated polytetrafluoroethylene is obtained; hexamethylenediamine is dissolved in a mixed solvent of anhydrous ethanol and deionized water to obtain a hexamethylenediamine grafting solution, wherein the volume ratio of anhydrous ethanol to deionized water is 8:2; the concentration of the hexamethylenediamine grafting solution is 0.1M, the surface activated polytetrafluoroethylene is immersed therein, the mass ratio of the surface activated polytetrafluoroethylene to the hexamethylenediamine is 1:10, and 0.5% of benzoyl peroxide by mass of the surface activated polytetrafluoroethylene is added to obtain a reaction solution A, the reaction is stirred at a constant temperature of 77°C for 1.2 hours, filtered, washed, and dried at 70°C for 20 hours to obtain amino-modified surface activated polytetrafluoroethylene;
[0141] S3: Dissolve xanthan gum in deionized water, stir at 32°C for 1.2h to obtain a xanthan gum solution, wherein the xanthan gum accounts for 2%; add pentanediol and tetrabutyl titanate to obtain a mixed solution A, wherein the added pentanediol accounts for 30% of the mass of the xanthan gum; the tetrabutyl titanate accounts for 0.5% of the mass of the xanthan gum, use sodium hydroxide solution to adjust the pH of the mixed solution A to 9.5 to obtain a reaction solution B, react in a 66°C constant temperature water bath for 3.2h, and after the reaction, cool the reaction solution B for standby use; add polyacrylic acid to deionized water to obtain a polyacrylic acid grafted solution with a concentration of 0.35g / mL, add glycidyl methacrylate to the polyacrylic acid grafted solution and stir to obtain a mixed solution B, wherein the mass ratio of glycidyl methacrylate to polyacrylic acid is 2:10, add azobisisobutyronitrile to obtain a reaction solution C, wherein azobisisobutyronitrile The mass ratio of diisobutyronitrile to polyacrylic acid is 1.8:100, and the mixture is stirred at a constant temperature of 70°C for 2 hours under a nitrogen and argon atmosphere. After cooling, anhydrous ethanol is added to precipitate, which is filtered, washed, and dried at 40°C for 24 hours to obtain epoxy group-modified polyacrylic acid; the epoxy group-modified polyacrylic acid is dissolved in deionized water to obtain an epoxy group-modified polyacrylic acid solution with a concentration of 0.06 g / mL, which is added to the cooled reaction solution B and stirred to obtain a mixed solution C, wherein the mass ratio of epoxy group-modified polyacrylic acid to xanthan gum is 1:2, and hexamethylene diisocyanate accounting for 5% of the mass of xanthan gum is added to the mixed solution C and stirred for 40 minutes to obtain a reaction solution D, which is stirred at a constant temperature of 68°C for 2.2 hours, and after cooling, anhydrous ethanol is added to precipitate, which is filtered, washed, and dried at 55°C for 16 hours to obtain modified xanthan gum;
[0142] S4: Disperse the modified xanthan gum in deionized water and stir to disperse it, wherein the stirring speed is 900 rpm; the time is 1.3 hours, then add the polar modified nanomaterial deposited by thin film, the surface activated high temperature resistant polymer modified by amine group and sodium dodecyl sulfate to obtain the reaction solution E, stir at 33°C for 40 minutes, and dry to obtain the high temperature resistant xanthan gum, wherein the drying temperature is 60°C and the time is 12 hours.
[0143] Comparative Example 1
[0144] This embodiment provides a high temperature resistant xanthan gum, which is different from Example 1 in that the mass fraction of the polar modified nano material deposited in the thin film in the high temperature resistant xanthan gum is adjusted to 15 parts. Compared with Example 1, the mass fraction of the polar modified nano material deposited in the thin film in this embodiment is increased by 7 parts, and the increased parts are deducted from the modified xanthan gum, the surface activated high temperature resistant polymer modified by the amino group, and the surfactant, so that the mass fraction ratios of the other components except the polar modified nano material deposited in the thin film remain unchanged. The mass fractions of the components of the adjusted high temperature resistant xanthan gum are as follows:
[0145]
[0146] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0147] Comparative Example 2
[0148] This embodiment provides a high temperature resistant xanthan gum, which is different from Example 1 in that the mass fraction of the polar modified nano material deposited in the thin film in the high temperature resistant xanthan gum is adjusted to 0.5 parts. Compared with Example 1, the mass fraction of the polar modified nano material deposited in the thin film in this embodiment is reduced by 7.5 parts, and the reduced mass fraction is supplemented in equal proportion to the mass fraction of the modified xanthan gum, the amino-modified surface-activated high temperature resistant polymer, and the surfactant, so that the mass fraction ratio of the other components except the polar modified nano material deposited in the thin film remains unchanged. The mass fractions of the components of the adjusted high temperature resistant xanthan gum are as follows:
[0149]
[0150] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0151] Comparative Example 3
[0152] This embodiment provides a high temperature resistant xanthan gum, which is different from Example 1 in that the mass fraction of the amine-modified surface-activated high temperature resistant polymer in the high temperature resistant xanthan gum material is adjusted to 20 parts. Compared with Example 1, the mass fraction of the amine-modified surface-activated high temperature resistant polymer in this embodiment is increased by 8 parts, and the increased parts are deducted from the modified xanthan gum, the polar modified nanomaterial deposited in the thin film, and the surfactant, so that the mass fraction ratios of the other components except the amine-modified surface-activated high temperature resistant polymer remain unchanged. The mass fractions of the components of the adjusted high temperature resistant xanthan gum are as follows:
[0153]
[0154]
[0155] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0156] Comparative Example 4
[0157] This embodiment provides a high temperature resistant xanthan gum, which is different from Example 1 in that the mass fraction of the surface activated high temperature resistant polymer modified by an amine group in the high temperature resistant xanthan gum is adjusted to 2 parts. Compared with Example 1, the mass fraction of the surface activated high temperature resistant polymer modified by an amine group in this embodiment is reduced by 10 parts, and the reduced mass fraction is supplemented in equal proportion to the mass fraction of the modified xanthan gum, the polar modified nanomaterial deposited in the thin film, and the surfactant, so that the mass fraction ratio of the other components except the surface activated high temperature resistant polymer modified by an amine group remains unchanged. The mass fractions of the components of the adjusted high temperature resistant xanthan gum are as follows:
[0158]
[0159] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0160] The performance test of the heat-resistant xanthan gum of the above-mentioned Examples 1-4 and Comparative Examples 1-4 was carried out, and the specific process is as follows:
[0161] The untreated xanthan gum was used as a blank control group, and the untreated xanthan gum and the high temperature resistant xanthan gum prepared in the above Examples 1-4 and Comparative Examples 1-4 were respectively prepared into solutions with a mass percentage concentration of 0.1%, treated at a high temperature of 120°C for 3 hours, then taken out and cooled to room temperature, and the viscosity was tested using a rotational viscometer at 100 rpm. The results are as follows: Figure 2 shown.
[0162] Depend on Figure 2 It can be seen that the high temperature resistant xanthan gum prepared in Examples 1-4 provided by the present invention has good thermal stability, which is conducive to the wide application of xanthan gum in high temperature scenarios such as high petroleum and food processing.
[0163] From the test results of Example 1 and Comparative Examples 1 and 2, it can be seen that an appropriate amount of thin film deposited polar modified nanomaterials can enhance the high temperature resistance of xanthan gum. When the content is too high, agglomeration may occur between particles, resulting in uneven dispersion, weakened interface effects, and even destruction of the structural continuity of the material. At the same time, a high content of nanomaterials may make the material brittle, resulting in decreased flexibility, and reduce the impact resistance of the material, which in turn weakens the high temperature resistance of xanthan gum.
[0164] From the test results of Example 1 and Comparative Examples 3 and 4, it can be seen that when the content of the surface-activated high-temperature resistant polymer modified by the amino group is too high, the interaction between the modified high-temperature resistant polymers may be too strong, resulting in a weakened interfacial bonding force with the xanthan gum. Under high temperature conditions, the brittleness of the material increases, which may cause stress concentration and structural damage; at the same time, a high content of high-temperature resistant polymers may form agglomeration in the xanthan gum matrix, affecting the uniformity of the material, causing premature thermal decomposition in local areas, and the overall high-temperature resistance performance is reduced.
[0165] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A high temperature resistant xanthan gum, characterized in that: The high temperature resistant xanthan gum comprises the following components in parts by weight: 60-80 parts of modified xanthan gum; 1-10 parts of polar modified nanomaterials for thin film deposition; 5-15 parts of amine-modified surface-activated high-temperature resistant polymer; Surfactant 0.1-2 parts.
2. The method for preparing a high temperature resistant xanthan gum according to claim 1, wherein: The preparation method is: S1: dissolving the polar group reagent in anhydrous ethanol, adding deionized water to obtain a polar group solution, adding the inorganic nanomaterial, stirring and dispersing, filtering, washing, and drying to obtain the inorganic nanomaterial with surface polarity modification; The inorganic nanomaterial with surface polarity modification is placed in a chemical vapor deposition device for deposition modification, and after the deposition is completed, the polarity-modified nanomaterial is obtained by drying the nanomaterial for thin film deposition; S2: placing the high temperature resistant polymer in an ultraviolet irradiation device for irradiation; cooling to obtain a surface activated high temperature resistant polymer; dissolving the amination reagent in a mixed solvent of anhydrous ethanol and deionized water to obtain an amination grafting solution, immersing the surface activated high temperature resistant polymer therein, and adding an amination catalyst to obtain a reaction solution A, stirring the reaction at a constant temperature, filtering, washing, and drying to obtain an amino-modified surface activated high temperature resistant polymer; S3: Dissolve xanthan gum in deionized water and stir to obtain a xanthan gum solution; add a polyol and a catalyst to obtain a mixed solution A, use a sodium hydroxide solution to adjust the pH of the mixed solution A to obtain a reaction solution B, react in a constant temperature water bath, and cool the reaction solution B for standby use after the reaction is completed; add a grafted polymer to deionized water to obtain a grafted solution, add an epoxy group donor to the grafted solution and stir to obtain a mixed solution B, add azobisisobutyronitrile to obtain a reaction solution C, stir at a constant temperature under an inert gas atmosphere, add anhydrous ethanol to precipitate after cooling, filter, wash, and dry to obtain an epoxy group-modified grafted polymer; dissolve the epoxy group-modified grafted polymer in deionized water to obtain an epoxy group-modified grafted polymer solution, add the epoxy group-modified grafted polymer to the cooled reaction solution B and stir to obtain a mixed solution C, add a cross-linking agent to the mixed solution C and continue stirring to obtain a reaction solution D, stir at a constant temperature, add anhydrous ethanol to precipitate after cooling, filter, wash, and dry to obtain a modified xanthan gum; S4: Dispersing the modified xanthan gum in deionized water and stirring to disperse, then adding the polar modified nanomaterial deposited by thin film, the surface activated high temperature resistant polymer modified by amine group and the surfactant to obtain the reaction solution E, stirring and drying to obtain the high temperature resistant xanthan gum.
3. The preparation method of heat-resistant xanthan gum according to claim 2, characterized in that, The polar group reagent is aminosilane and / or 3-aminopropyltriethoxysilane; The volume fraction of the polar group reagent in the polar group solution is 2-5%; The amount of deionized water added is 0.5-1 mL; The inorganic nanomaterial is nano silicon dioxide and / or nano aluminum oxide; The mass ratio of the polar group reagent to the inorganic nanomaterial is 1:(3-5); The time for stirring and dispersing the inorganic nanomaterial after it is added into the polar group solution is 40-60 minutes.
4. The preparation method of heat-resistant xanthan gum according to claim 2, characterized in that, The drying temperature of the surface polarity modified inorganic nanomaterial is 50-60°C; The drying time of the surface polarity modified inorganic nanomaterial is 24-30 hours; The temperature for depositing and modifying the surface polarity-modified inorganic nanomaterial is 250-350° C.; The surface polarity modified inorganic nanomaterial is deposited and modified for 1-2 hours; The gas pressure for depositing and modifying the surface polarity-modified inorganic nanomaterial is 1-5 Torr; The gas source for the deposition modification of the inorganic nanomaterial with surface polarity modification is silane and / or dimethylsilane; The temperature for drying the polar modified nanomaterial deposited in the thin film is 70-80°C; The drying time of the polar modified nanomaterial deposited in the thin film is 8-12 hours.
5. The preparation method of heat-resistant xanthan gum according to claim 2, characterized in that, The high temperature resistant polymer is any one of polytetrafluoroethylene, polyimide or polyetheretherketone; The wavelength of the ultraviolet light source in the ultraviolet irradiation equipment is 220-260nm; The ultraviolet light intensity in the ultraviolet light irradiation device is 10-20W / cm 2 ; The ultraviolet light irradiation time in the ultraviolet light irradiation equipment is 15-30 minutes; The amination reagent is ethylenediamine and / or hexamethylenediamine; The volume ratio of anhydrous ethanol and deionized water in the mixed solvent of the aminated grafting solution is (7:3)-(9:1); The concentration of the amination agent in the amination grafting solution is 0.1-1.0M.
6. The preparation method of heat-resistant xanthan gum according to claim 2, characterized in that, The mass ratio of the surface activated high temperature resistant polymer to the amination reagent is 1:(5-10); The amination catalyst is benzoyl peroxide and / or dicumyl peroxide; The amination catalyst accounts for 0.1-0.5% of the mass of the surface activated high temperature resistant polymer; The temperature of the reaction solution A being stirred at a constant temperature is 60-80°C; The reaction solution A is stirred at a constant temperature for 1-2 hours; The drying temperature of the amino-modified surface-activated high-temperature resistant polymer is 60-70°C; The drying time of the amino-modified surface-activated high-temperature-resistant polymer is 20-30 hours.
7. The preparation method of heat-resistant xanthan gum according to claim 2, characterized in that, The xanthan gum in the xanthan gum solution accounts for 1-2%; The temperature at which the xanthan gum solution is stirred is 25-35° C.; The xanthan gum solution is stirred for 1-2 hours; The polyol is ethylene glycol and / or pentanediol; The polyol accounts for 20-30% of the mass of the xanthan gum; The catalyst is tetrabutyl titanate and / or tetraisopropyl titanate; The catalyst accounts for 0.1-0.5% of the mass of the xanthan gum; The pH of the mixed solution A is adjusted to 8-10 to obtain a reaction solution B; The temperature of the reaction solution B in a constant temperature water bath is 50-70°C; The reaction time of the reaction solution B in a constant temperature water bath is 3-4 hours.
8. The preparation method of heat-resistant xanthan gum according to claim 2, characterized in that, The graft polymer is polyvinyl alcohol and / or polyacrylic acid; The concentration of the grafting solution is 0.2-0.4 g / mL; The epoxy group donor is ethylene oxide and / or glycidyl methacrylate; The mass ratio of the epoxy group donor to the grafted polymer is (1-2):10; The mass ratio of azobisisobutyronitrile to the grafted polymer is (1-2): 100; The inert gas is nitrogen and / or argon; The temperature of the reaction solution C being stirred at a constant temperature is 60-70°C; The reaction solution C is stirred at a constant temperature for 2-3 hours; The drying temperature of the epoxy group modified graft polymer is 40-50°C; The drying time of the epoxy group-modified graft polymer is 18-24 hours.
9. The preparation method of heat-resistant xanthan gum according to claim 2, characterized in that, The concentration of the epoxy group modified graft polymer solution is 0.04-0.08 g / mL; The mass ratio of the epoxy group-modified graft polymer to the xanthan gum in the mixed solution C is 1:(1-2); the cross-linking agent is glutaraldehyde and / or hexamethylene diisocyanate; The cross-linking agent accounts for 3-5% of the mass of the xanthan gum; After adding the cross-linking agent to the mixed solution, continue stirring for 30-40 minutes; The temperature of the reaction solution C being stirred at a constant temperature is 60-70°C; The reaction solution C is stirred at a constant temperature for 2-3 hours; The temperature for drying the modified xanthan gum is 50-60°C; The modified xanthan gum is dried for 12-18 hours.
10. The preparation method of heat-resistant xanthan gum according to claim 2, characterized in that, The modified xanthan gum is dispersed in deionized water and stirred at a speed of 500-1000 rpm; The modified xanthan gum is dispersed in deionized water and stirred for 1-2 hours; The surfactant is sodium lauryl sulfate and / or polyvinyl pyrrolidone; The stirring temperature of the reaction solution D is 25-35°C; The stirring time of the reaction solution D is 30-60min; The temperature for drying the high temperature resistant xanthan gum is 50-60°C; The drying time of the high temperature resistant xanthan gum is 12-24 hours.